2002
DOI: 10.1097/00005537-200209000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Esophagitis in Patients With pH‐Documented Laryngopharyngeal Reflux

Abstract: In the present series of patients with documented laryngopharyngeal reflux the prevalence of esophagitis and Barrett's metaplasia was only 19%. These data confirm the clinical impression that the patterns, mechanisms, and manifestations of laryngopharyngeal reflux differ from those of classic gastroesophageal reflux disease. Unlike gastroesophageal reflux disease, patients with laryngopharyngeal reflux uncommonly have esophagitis. Thus, although esophagoscopy may be an excellent method for screening the esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
78
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 16 publications
10
78
2
3
Order By: Relevance
“…However, it is not the exam of choice for diagnosing laryngopharyngeal reflux. Our results are similar to findings of some other authors (14,16) . Esophageal motor activity revealed that LES average pressure did not differ between patients with dysphonia and controls.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, it is not the exam of choice for diagnosing laryngopharyngeal reflux. Our results are similar to findings of some other authors (14,16) . Esophageal motor activity revealed that LES average pressure did not differ between patients with dysphonia and controls.…”
Section: Discussionsupporting
confidence: 94%
“…But, these authors did not exclude of the study, individuals using alcohol and tobacco, both factors that can cause lesions on larynx (18,22,32) . Female patients were more numerous among refluxers with dysphonia than in the control group (P = 0.047), as found by several authors (2,14,18,30) . Patients with dysphonia were older (46.8 ± 12.1 years) than the controls (39.1 ± 10.7 years; P = 0.02), suggesting a longer time of aggression to larynx epithelium.…”
Section: Discussionsupporting
confidence: 75%
“…[12] Contrary to GER, complaints of heartburn and regurgitation are not frequently encountered in LPR. [13,14] Ossakow et al [11] reported that patients with complaints of reflux had been either treated in the outpatient clinics of ENT (earnose and throat) (n=63) or gastroenterology (GE) (n=36). The authors also compared signs and symptoms of the cases and detected episodes of hoarseness in 100% of ENT cases (in none of GE patients), while the corresponding rates of heartburn in the ENT and GE groups were reported in 6 and 89% of the cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, practical algorithms of history taking and differential diagnosis to be used for the diagnosis of LPR are needed. [5,8,10,13,15] In order to be able to evaluate LPR symptoms and their severity Belafsky et al [3] described a reflux finding scoring (RFS) system which interrogated frequently encountered 8 symptoms of LPR. Scores of RFS ranges from 0 to 26 points.…”
Section: Discussionmentioning
confidence: 99%
“…Pepsin has been recognized as the true marker and the responsible factor of mucosal damage [8][9][10][11][12]13]. Pepsin is a proteolytic enzyme originated in the stomach; it is present within the acid vapors.…”
Section: Introductionmentioning
confidence: 99%